Oral Inflammation and Human Papilloma Virus Association among Hispanics - Maira A. Castañeda-Avila; Cynthia M. Pérez; José Vivaldi; Elba C. Díaz-Toro; Jeslie M. Ramos-Cartagena; Oelisoa M. Andriankaja; Ana P. Ortiz (International Journal of Dentistry)
Background. Identifying factors related to persistent human papillomavirus (HPV) infection is essential to reduce the incidence of HPV-related cancers. Objective. To evaluate whether gingival/periodontal inflammation is associated with oral HPV infection. Methods. This cross-sectional study (n = 740) uses data from the follow-up visit of the San Juan Overweight Adults Longitudinal Study, which recruited overweight/obese adults aged 40–65 from Puerto Rico. Participants completed a dental examination and two interviews (face-to-face/ACASI) and provided oral rinse samples for HPV detection. Oral inflammation was assessed using two definitions: (1) the number of sites with bleeding on probing (BOP), and (2) the number of teeth with probing pocket depths (PPD) ≥ 4 mm and BOP. Multivariate logistic regression was used to assess the association between oral inflammation and oral HPV. Results. Nearly three-quarters (72%) of participants were female, and 68% had 50 years or older. Participants with HPV had a higher mean number of sites with BOP (15.5 vs. 10.1) and teeth with PPD ≥ 4 mm and BOP (8.5 vs. 3.2) than participants without HPV (p<0.05). After adjusting for sex, age, income, and the number of oral sex partners, the odds of having an oral HPV infection increased by 3% (95% confidence interval (CI): 1.00–1.06) for any additional sites with BOP and 5% (95% CI: 1.02–1.09) for any other teeth with PPD ≥ 4 mm and BOP. Conclusions. We found that oral inflammation was associated with oral HPV infection among adults in Puerto Rico. Future studies need to further investigate the underlying mechanisms.